Super-hydrophobic cold surface air condensation water production device - RONG WANTING (2025)
The invention discloses a super-hydrophobic cold surface air condensation water production device, and relates to the technical field of air condensation water production devices. A connecting shaft is rotatably connected to the inner wall of the air inlet pipe in a penetrating mode, an impeller is fixedly installed on the connecting shaft, the connecting shaft is provided with a transmission mechanism, the transmission mechanism is used for controlling rotation of a cam, the protruding face of the cam is connected with a circulating mechanism, and the circulating mechanism is arranged in a condensation plate; the circulating mechanism is used for controlling the temperature of the surface of the condensing plate, the condensing plate is fixedly installed on the connecting rod and is inclined, a water collecting tank is arranged below the inclined direction of the condensing plate, and a filter screen is movably installed above the water collecting tank. The circulating speed of the cooling liquid can be auto